Dance displays in gibbons: biological and linguistic perspectives on structured, intentional, and rhythmic body movement - Coye, Camille; Caspar, Kai R; Patel-Grosz, Pritty (Primates; journal of primatology, 2025)
Female crested gibbons (genus Nomascus) perform conspicuous sequences of twitching movements involving the rump and extremities. However, these dances have attracted little scientific attention and their structure and meaning remain largely obscure. Here we analyse close-range video recordings of captive crested gibbons, extracting descriptions of dance in four species (N. annamensis, N. gabriellae, N. leucogenys and N. siki). In addition, we report results from a survey amongst relevant professionals clarifying behavioural contexts of dance in captive and wild crested gibbons. Our results demonstrate that dances in Nomascus represent a common and intentional form of visual communication restricted to sexually mature females. Whilst primarily used as a proceptive signal to solicit copulation, dances occur in a wide range of contexts related to arousal and/or frustration in captivity. A linguistically informed view of this sequential behaviour demonstrates that movement within dances is organized in groups and follows an isochronous rhythm - patterns not described for visual displays in other non-human primates. We argue that applying the concept of dance to gibbons allows us to expand our understanding of communication in non-human primates and to develop hypotheses on the rules and regularities characterising it. We propose that crested gibbon dances likely evolved from less elaborate rhythmic proceptive signals, similar to those found in siamangs. Although dance displays in humans and crested gibbons share a number of key characteristics, they cannot be assumed to be homologous. Nevertheless, gibbon dances represent a striking model behaviour to investigate the use of complex gestural signals in hominoid primates.
Keywords: Video Recording; komunikace zvířat; Animals; Animal Communication; Movement; Super linguistics; Female; audiovizuální záznam; zvířata; Isochrony; Dancing; Primate communication; pohyb; Small apes; Hylobates; tanec; ženské pohlaví; Dance syntax